Extent of peri-infarct scar on late gadolinium enhancement cardiac magnetic resonance imaging and outcome in patients with ischemic cardiomyopathy - Tueluemen, Erol; Rudic, Boris; Ringlage, Hannah; Hohneck, Anna; Röger, Susanne; Liebe, Volker; Kuschyk, Jürgen; Overhoff, Daniel; Budjan, Johannes; Akın, Ibrahim; Borggrefe, Martin; Papavassiliu, Theano (Heart rhythm, 2021)
Background - Only a minority of patients who receive an implantable cardioverter-defibrillator (ICD) on the basis of left ventricular ejection fraction receive appropriate ICD therapy. Peri-infarct scar zone assessed by late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) is a possible substrate for ventricular tachyarrhytmias (VTAs). - Objective - The aim of our prospective study was to determine whether LGE-CMR parameters can predict the occurrence of VTA in patients with ischemic cardiomyopathy (ICM). - Methods - Two hundred sixteen patients with ICM underwent CMR imaging before primary or secondary ICD implantation and were prospectively followed. We assessed CMR indices and CMR scar characteristics (infarct core and peri-infarct zone) to predict outcome and VTAs. - Results - Patients were followed up for 1497 days (interquartile range 697-2237 days). Forty-seven patients (21%) received appropriate therapy during follow-up. Patients with appropriate ICD therapy had smaller core scar (31.5% ± 8.5% vs 36.8% ± 8.9%; P = .0004) but larger peri-infarct scar (12.4% ± 2.6% vs 10.5% ± 2.9%; P = .0001) than did patients without appropriate therapy. In multivariate Cox regression analysis, peri-infarct scar (hazard ratio 1.15; 95% confidence interval 1.07-1.24; P = .0001) was independently and significantly associated with VTAs whereas left ventricular ejection fraction, right ventricular ejection fraction, core scar, and left atrial ejection fraction were not. - Conclusion - Scar extent of peri-infarct border zone was significantly associated with appropriate ICD therapy. Thus, LGE-CMR parameters can identify a subgroup of patients with ICM and an increased risk of life-threatening VTAs.